The pros and cons of government regulation - Joseph L. Porket (Institute of Economic Affairs (IEA), 2003)
Regulation of human behaviour and human social interaction is a universal feature of both traditional and modern societies. In the latter, on account of their complex structure, regulation inevitably takes place at different levels, albeit within a framework set by government. Consequently, these societies are characterised by a web of formal as well as informal regulation and self-regulation, in other words by a plurality of regulatory systems. And this plurality of regulatory systems is an important source of tensions and conflicts in society.
Keywords: 330; Society; Government; Regulation; Gesellschaft; Regierung; Regulierung